Fungsi dan Peran Guru Pendidikan Agama Islam untuk Peningkatkan Kedisiplinan Pelaksanakan Sholat Berjamaah Siswa - Ahmad Ridwan; Delvira Asmita; Neiny Puteri Wulandari (Departement of Mathematics Education, 2023)
This paper examines the role of Islamic religious education teachers in improving the discipline of congregational prayers. The author focuses this paper on the role of Islamic religious education teachers in improving the discipline of congregational prayers. Teachers play an important role in guiding student behavior to achieve learning goals. The same is true in carrying out prayer services, because a teacher is not only a facilitator who is obliged to provide information about various matters regarding knowledge. Islamic religious education is a professional educator who has the task of educating, teaching and guiding students in schools in understanding and practicing Islamic religious teachings. Discipline is an exercise in forming or perfecting and carrying out certain patterns of behavior to comply with rules or regulations accompanied by awareness and sincerity. Discipline in carrying out congregational prayers is perfecting or carrying out congregational prayers on time. Discipline in prayer means practice that forms, straightens, or perfects the implementation of prayer both in the procedure for carrying it out and in the discipline of its implementation. Discipline in prayer can also mean efforts to shape one's behavior to be disciplined in prayer implementation, both movement, reading and also the time of its implementation. Therefore, Islamic religious education teachers play a very important role and have a function in increasing the discipline of praying in congregation of students..